All-of-a-kind family Hanukkah - Jenkins, Emily, 1967- (Schwartz & Wade books, 2018)
In 1912 New York, Gertie feels left out while Mama and her four older sisters cook Hanukkah dinner, but Papa comes home and asks her help with an important task.